Peripheral ossifying fibroma of the anterior maxillary gingiva - Ganendra Anugraha; Ni Putu Mira Sumarta (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Peripheral ossifying fibroma is a rejuvenation of the reactive gingiva, usually occurring in the anterior maxillary gingiva. The condition is often clinically ambiguous when diagnosed on the basis of gingival hyperplastic lesions such as focal fibrous hyperplasia, peripheral giant cell granuloma, peripheral fibroma and pyogenic granuloma because peripheral ossifying fibroma has a tendency to recur with a ratio of around 20%. The literature on the subject predominantly classifies peripheral osifying fibroma as an epulis type, but it has also been identified as a peripheral mesenchymal tumor presenting similar clinical symptoms to ossified fibrous epulis. Purpose: The purpose of this article is to explain the rare case of peripheral ossifying fibroma in the anterior maxillary gingiva which can be clinically misdiagnosed as reactive gingival hyperplastic lesions. Case: A case report of peripheral ossifying fibroma in the left lateral incisor and canine of the maxillary gingiva in a 26 year-old male. The patient chiefly complained of a painless, slow growing gingival enlargement on the upper left jaw during the previous five years. Clinical examination confirmed it to be a single, hard swelling in the 21-24 region, pale in color and with a rough surface. Case management: The procedure constituted a complete surgical excision of the lesion together with the underlying periosteum curettage intended to prevent recurrence. The histopathologic examination results indicated tissue with squamous epithelial lining, stroma consisting of fibroblasts, and immature trabecula with osteoblastic rimming between collagen tissue without signs of malignancy. Osteoblastic rimming has specific features in histopathologic examination of ossifying fibroma. Conclusion: Peripheral ossifying fibroma is a rare solitary enlargement in the oral cavity frequently misdiagnosed as ossified fibrous epulis. A definitive diagnosis is made by means of histopathologic examination. The condition has a low reccurance rate.